Northeast political elites and the regional development model - Ismael, Ricardo (Universidade Estadual Paulista / UNESP, 2020)
This article intends to make a comparative study on the vision of the Northeast state political elites, especially the ones involving the governing groups of Bahia, Pernambuco and Ceará, from 1995 to 1998, about the federalist model and about the redefinition of the model of regional development. In the last decade of the last century, in the context of the Federal Constitution of 1988, Brazilian federalism has moved towards more competition and less cooperation, despite the constitutional tax transfers from the Union to the less developed regions, and the presence of federal institutions with regional level. The underlying hypothesis is that the governors of the most economically developed states disagreed over changes in the form of federal government intervention in the region, reflecting the existing and conflicting political and economic interests and ongoing changes in the more general federative dynamic.